Medicinal Plants and Traditional Medical Practices in Nepal - Shrestha, Krishna K.; Kunwar, Ripu M. (Annapurna Journal of Health Sciences, 2023)
The World Health Organization has encouraged using indigenous and traditional medical practices of their own which have been practicing since many centuries. As a result, the medicinal plants of Nepal are nowadays revalued by extensive researches on medicinal plant species and their therapeutic principles, to ascertain safety and efficacy of traditional medicines and admit the benefits of medical pluralism. We reviewed the therapeutically useful plant species and assessed their value to consider them as a potential resource for complementary and alternative medicine in Nepal. Medicinal plants used for top ten disorders of Nepal followed by medicinal plants prioritized for conservation by Herbs and NTFPs Coordination Committee, selection criteria for DNA barcoding of plants in Nepal, and frequently referred to the earlier literature were reviewed and presented 100 highly valued medicinal plant species. The species are being used in rural and local pharmacopoeias, and they are potential in bioprospecting and pharmacology and drug discovery in Nepal. Different therapeutic traditions coexist in Nepalese medical system where people can opt medicine based on their preferences, cultural backgrounds and their specific illnesses, which we admit as a win-win situation for well-being of citizens. Communication of traditional useful medicinal plant species and their scopes of primary health care abridges traditional and modern medicines, and lay ground for medical pluralism.